PERAN PUBLIC RELATIONS DALAM MEMPENGARUHI KONTEN MEDIA - Hidayat, Rizki (Interaksi: Jurnal Ilmu Komunikasi, 2016)
AbstractIn this era of globalization of business competition is getting higher. Especially in economic sectors where big companies from abroad increasingly free to operate and market its products in Indonesia so that local companies can not compete with itself would be eliminated. The purpose of this study was look at the effectiveness of IT utilization is also the creativity of a public relations. Popularity of media and social networks such as Facebook, Twitter, YouTube, spur the growth of "medium alone" that allows companies and organizations to set up reporting directly or through intermediaries and remediation (where, the media took the headlines of social media and republish). The results of this study indicate that the majority of social media is 'parasitic', take a lot of information and topics of the mass media. Public relations in general is a process of communication management activities to create mutual understanding between an organization and its publics. Â Keyword : public relations, media ethics, media content Â Â